Foodborne disease hazards and burden in Ethiopia: A systematic literature review, 1990–2019 - Gazu, Lina; Alonso, Silvia; Mutua, Florence K.; Roesel, Kristina; Lindahl, Johanna F.; Amenu, Kebede; Sousa, F.M.; Ulrich, P.; Guadu, T.; Dione, Michel M.; Ilboudo, Guy S.; Knight-Jones, Theodore J.D.; et al. (Frontiers Media, 2023)
Background: Foodborne disease (FBD) affects millions of people each year, posing a health burden similar to malaria, tuberculosis or HIV. A recent World Bank study estimated the productivity losses alone attributed to unsafe food within Africa at $20 billion in 2016, and the cost of treating these illnesses at an additional $3.5 billion. Ethiopia faces multiple food safety challenges due to lack of infrastructure and basic pre-requisites for food safety such as clean water and environment, washing facilities, compounded by limited implementation of food safety regulations, and a lack of incentives for producers to improve food safety. A consolidation of our understanding and evidence of the source, nature and scale of FBD in Ethiopia is needed to inform policy and future research. We performed a Systematic Literature Review (SLR) of publications on FBD occurrence in Ethiopia including hazard presence and impact.